Toward the Promised Land : Politicisation as a Pathway to Emancipatory Agricultural Transformation in Uganda - Byaruhanga, Ronald (Lund University (Media-Tryck), 2025)
Amid escalating ecological crises, widening socio-economic inequalities, and intensifying climate change, the imperative to transform agricultural systems towards sustainability and equity has become increasingly urgent. Yet such transformation is often hindered by entrenched institutional and structural arrangements that privilege narrowly defined notions of productivity and market efficiency, thereby sidelining holistic approaches that emphasise resilience, equity, and human and ecological flourishing. Consequently, although pathways such as agroecology are gaining traction as viable alternatives, their adoption and expansion remain constrained. Against this backdrop, this thesis proceeds from the premise that realising such transformative alternatives requires confronting and disrupting the institutional, structural, and political obstacles that impede change. In this thesis, I explore the potential of politicisation as a process through which dominant agricultural development practices and ideologies are reframed and contested in Uganda. Specifically, I investigate how politicisation unfolds and how it shapes the possibilities for advancing transformative agricultural alternatives, including efforts to reconfigure the institutional arrangements that structure agricultural systems. Grounded in critical realism, emancipatory social science, and social movement theory, the analysis seeks to uncover the underlying mechanisms and structural conditions that shape how social actors mobilise, exercise agency, and generate transformative social power. I examine how these actors challenge and reconfigure dominant agrarian models while navigating and negotiating political constraints, thereby illuminating the dynamic processes through which collective action and emancipatory transformation become possible. The thesis comprises three interlinked articles that collectively demonstrate how, despite entrenched institutional and political barriers, change agents carve out spaces and leverage existing openings to prefigure and advocate for alternative practices and visions. These strategies are anchored in adaptive, often non-confrontational practices that balance resistance with collaboration, illustrating how change agents navigate tensions between transformative aspirations and structural constraints without relinquishing their critical stance. With these findings, the thesis offers both theoretical and empirical contributions. Theoretically, it conceptualises politicisation as a mechanism that not only challenges and reframes agricultural transformation but also enables change agents to create the conditions necessary to navigate constraints while insulating themselves against co-optation and repression. Empirically, it demonstrates how political mobilisation materialises in contexts where open confrontation is restricted, showing how actors cultivate collective agency and expand the possibilities for transformative change. Overall, the thesis argues that politicisation involves both material and discursive practices through which emancipatory agricultural transformation can emerge across diverse contexts and conditions.
Keywords: agricultural development; politicisation; agroecology; Food sovereignty; Smallholder farmers; sustainability science; Uganda